(untitled) (American Journal of Technology and Applied Sciences, 2026)
The interdisciplinary integration of scientific subjects has become an important approach in modern education, enabling students to develop a holistic understanding of natural phenomena. This article examines the integration of physics and chemistry in teaching chemical bonding and valence within the context of atomic physics. The study explores how concepts of atomic structure, electron configuration, quantum mechanics, and electromagnetic interactions provide a physical basis for understanding chemical bonds and valence. Particular attention is given to interdisciplinary teaching methods that connect theoretical knowledge from physics and chemistry, promoting deeper conceptual understanding and scientific literacy.